Critical Thinking and Higher Education: A Historical, Theoretical and Conceptual Perspective - Katende, Esther (Journal of Education and Practice, 2023)
Purpose: The purpose of this Study is to analyze the historical, theoretical and conceptual basis of the critical thinking in relation to higher education. Methodology: The methodology used is a review of existing literature on critical thinking and higher education. Findings: The study shows that critical thinking is embedded in Bloom's Taxonomy and institutions of higher education that implement the higher levels of Bloom's taxonomy embrace critical thinking in their curriculum. Unique contributor to theory, policy and practice: The study presents a unique contribution to theory by relating Bloom's Taxonomy to critical thinking.